Chitosan-triphosphate nanoparticles for encapsulation of super-paramagnetic iron oxide as an MRI contrast agent - Chutimon Sanjai (2018)
Super-paramagnetic iron oxide nanoparticles (SPIONPs) were encapsulated at various concentrations within chitosan-triphosphate (SPIONPs-CS) nanoparticles using an ionotropic gelation method. The encapsulation of SPIONPs within CS nanoparticles enhanced their dispersion ability in aqueous solution, with all particles being lower than 130 nm in size and having highly positive surface charge. The SPIONPs-CS nanoparticles exhibited crystalline structure and super-paramagnetic behavior, as seen in non-encapsulated SPIONPs. The morphology of SPIONPs-CS nanoparticles showed that they almost spherical in shape. The effect of phantom environments (culture medium and 3% agar solution) on either T1or T2weighted MRI was investigated using a clinical 1.5 T MRI scanner. The results revealed that 3% agar solution showed relaxation values higher than the culture medium, leading to a significant decrease in the MR image intensity. Our results demonstrated that the SPIONPs-CS nanoparticles can be applied as tissue-specific MRI contrast agents. © 2014 Elsevier Ltd. All rights reserved.